2021
DOI: 10.3390/molecules26247471
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone Changes in Immature and Mature Soybeans by Thermal Processing

Abstract: The isoflavone changes occurring in mature soybeans during food processing have been well studied, but less information is available on the changes in immature soybeans during thermal processing. This study aimed to determine the effect of thermal processing by dry- or wet-heating on the changes in the isoflavone profiles of immature and mature soybeans. In the malonylglycoside forms of isoflavone, their deglycosylation was more severe after wet-heating than after dry-heating regardless of the soybean maturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, hot-air drying is one of the most commonly employed heat treatments that alters not only the physical properties (such as hardness) but also the chemical properties (such as polyphenol decomposition) of food materials. Heat treatment increases taste preferences by promoting nonenzymatic reactions in food or inducing a change in flavor components [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Heat treatment can cause an increase in phenolic compounds and antioxidant activity in various fruit crops such as citrus, persimmon peel, and eggplant fruit [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hot-air drying is one of the most commonly employed heat treatments that alters not only the physical properties (such as hardness) but also the chemical properties (such as polyphenol decomposition) of food materials. Heat treatment increases taste preferences by promoting nonenzymatic reactions in food or inducing a change in flavor components [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Heat treatment can cause an increase in phenolic compounds and antioxidant activity in various fruit crops such as citrus, persimmon peel, and eggplant fruit [ 10 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds can be increased or decreased depending on the crops, maturity, and processing methods. It was reported that the phenolic content decreased as the olive fruit matured, while it increased as soybean seed matured [ 9 , 22 ]. Moreover, the total phenolic content decreased during thermal processing in the flesh of persimmon fruit with the decrease in antioxidant activity, while it increased in the peel [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The kaempferol contents in LG and LR increased from 446.73 μg/g DW and 93.80 μg/g DW in the NGS after a 30 °C treatment to, respectively, 482.87 μg/g DW and 163.81 μg/g DW after treatments at higher temperatures. During heat processing, either the release of bound flavonoids or the acceleration of the extract ratio might account for this sort of increase [ 24 , 28 , 37 ]. The GS showed relatively low level of flavonoids in comparison with the NGS ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the different progressions of thermal processing (methods, time, temperature, etc.) affecting different substances [ 13 , 37 , 38 , 39 , 40 , 41 ], as Rk3 and Rh4 are the deglycosylated products of Rg6 and F4 at C-6, respectively. Ginsenoside mutations in ginseng leaves during heat treatment have not been widely studied in the literature, especially in terms of dry-heat treatment.…”
Section: Resultsmentioning
confidence: 99%